ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PERUSAHAAN (STUDI EMPIRIS : PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014) - B31110017, ISNAINI (Jurnal Manajemen Update, 2016)
This research was carried out to examine the effect of the variable of Working Capital To Total Assets (WCTA), Debt To Equity Rasio (DER), Total asset Turnover (TAT), and Net Profit Margin (NPM) on the growth of profit. The data were obtained through the method of purposive sampling with the following criteria : (1) Manufacturing companies listed on the Indonesian Stock Exchange (IDX) and were consistently there during the research period (2010 through 2014), (2) Manufacturing companies that published financial statements during the research period from 2010 to 2014, (3) Manufacturing companies which had positive earnings and variables during the period from 2010 to 2014, (4) Manufacturing companies whose financial data used the Indonesian rupiah currency. The results of analysis showed that the data used in this research have fulfilled the classical assumption, which include : having no signs of heteroscedasticity, being significant on linierity, and the data being normally distributed. The result of regression analysis indicated that the variables of Working Capital To Total Assets (WCTA) and Total Asset Turnover (TAT) dan Net Profit Margin (NPM) partially had a positive significant effect on the growth to profit of manufacture company. Meanwhile, the variable of Debt Equity Ratio (DER) had a negative insignificant effect on the growth of profit. The predictive ability of the four variables simultaneously was 36.8% of the total existing independent variables, while 63.2% was influenced by variables other indevendent not know and studied scientifically had a effect on the growth of profit. Keywords : Working Capital to Total Assets (WCTA), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), Net profit Margin (NPM), and Growth of Profit.